Listening to the Past: Archaeology, Oral History, and Memoryscapes in the Koya Region (Iraq) - Pappi, Cinzia; Awmar, Nyaz Azeez (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2025)
This paper explores how archaeology in the Kurdish Region of Iraq is being redefined through the integration of oral history and community engagement, focusing on the case studies conducted within the Archaeological Survey of Koisanjaq/Koya (ASK) project. By combining remote sensing, field archaeology, and structured interviews, the project examines how local communities perceive, inhabit, and reinterpret the archaeological landscape. Special attention is given to Qala Shila, Gird-i Chragh, Ashti, and Qazbajian/Gazbagi—sites that illustrate the intertwined dynamics of memory, resilience, and socio-economic transformation in the Koya region. The analysis demonstrates how oral testimonies serve not merely as ethnographic data but as active instruments for refining archaeological interpretation, monitoring site preservation, and enhancing cultural awareness. Drawing on the conceptual frameworks of memoryscapes and taskscapes, this study argues that archaeological landscapes in Iraqi Kurdistan are simultaneously places of work and remembrance, where ancient material traces and modern experiences coexist. The ASK project thus contributes to a broader methodological shift toward participatory archaeology, where scientific inquiry and local narratives converge to foster inclusive heritage management. By embracing this approach, archaeology becomes not only a means of reconstructing the past but also a platform for building sustainable relationships between communities and their cultural landscapes.